Sacral window for the surgery of L5 neurofibroma - Kaplan, Metin; Oezveren, Mehmet Faik (Turkish Neurosurgical Soc, 2007)
OBJECTIVE: To describe a way to increase the exposure for L5-S1 neurofibroma extending to presacral area. Summary of Background Data: Since the neurofibromas of L5-S1 level generally extend to the extraforaminal and presacral area, their resection is difficult compared to other lumbar levels. METHODS: A 46-year-old female presented with severe pain in her left leg. There was a mild motor power loss in her left ankle and toe at plantar and dorsiflexion, and a mild hypoesthesia in the posterior of the left foot and its base. Lumbar computed tomography and magnetic resonance imaging showed a mass in the left intervertebral foramen extending to the extraforaminal presacral area at the level of L5-S1. The tumor was removed through a surgical bone window in the base of the sacrum and resection of L5 transverse process on the left side. RESULT. The tumor was removed totally. Following surgery, the patient's pain had totally disappeared and there was no alteration in her neurological status. CONCLUSION: L5-S1 neurofibroma was totally resected through a surgical window in the base of the sacrum.
Keywords: neurofibroma; sacrum; surgical approach